Screening Programming’s Reliability to Measure Predictive Programming Skills - Dantas, Danilo Medeiros; Santos, Jucelio Soares dos; Dantas, Kézia de Vasconcelos Oliveira; Andrade, Wilkerson L.; Brunet, João; Melo, Monilly Ramos Araujo (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2023: Anais do XXXIV Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/sbie.2023.235112, 2023)
This study aimed to evaluate the reliability of an item bank developed in the Screening Programming system for measuring predictive programming skills. The results revealed that the selected items showed good content analysis and consistent psychometric properties. Furthermore, the instruments created from this item bank demonstrated good reliability in professional assessments, validating their accuracy and stability across different contexts and populations. These findings contribute to the programming field by providing a reliable instrument for assessing and developing predictive skills in this domain, fostering continuous advancements in understanding and teaching these skills.